Some Characterizations of (m,μ)-Precontinuous Functions: Kittiya Wanwongsa, Chokchai Viriyapong, Chawalit Boonpok - Team, Support (Thai Journal of Mathematics, 2016)
The aim of this paper is to introduce a weak froms of (m, μ)-continuous functions, which are called (m, μ)-precontinuous, almost (m, μ)-precontinuous and weakly (m, μ)-precontinuous, as funtions from an m-space into a generalized topological space. Several characterizations of functions are obtained.